A high sense of coherence protects from the burden of caregiving in older spousal caregivers. (March 2018) - Potier, Florence; Degryse, Jean-Marie; Henrard, Séverine; Aubouy, Geneviève; de Saint-Hubert, Marie
Highlights: 69% of the caregivers consider caregiving as a source of self-fulfillment. Spouse functional limitations were associated with a higher burden. Caregivers with a higher SOC-13 reported a significantly lower burden. In our study, SOC did not appear to be merely the inverse of depression. Abstract: Objectives: Caregiving is often associated with burden and chronic stress. Sense of coherence (SOC) may help the caregivers in coping with their stress and was identified as a positive factor for health outcomes and quality of life. We aimed to study the links between SOC, burden, depression and positive affects among caregivers of frail older patients. Methods: Seventy-nine spousal caregivers were recruited via the geriatric outpatient clinic. Data collected: Zarit Burden Inventory, SOC-13, Geriatric Depression Scale, Caregiver Reaction Assessment (CRA), sleep, time of supervision, Katz Index, Global Deterioration Scale and Neuropsychiatric Inventory. Analyses: Caregiver's characteristics were analyzed by burden severity and SOC level. Multivariable logistic regressions were used in order to identify the variable that best predict caregiver burden and high SOC. Results: The mean age was 79.4 ± 5.3; 53% were women. Among care-recipient, 82% had cognitive impairment and the median Katz Index was 3. Caregivers with a high SOC and an older age reported a lower burden (Odds Ratio (OR) 0.18, 95% confidence interval (CI) 0.04–0.65 and OR 0.87, 95% CI 0.76–0.98, respectively). A higher burden was associated with patient functional limitations (OR 8.69, 95% CI 2.28–40.46). Discussion: Having a high sense of coherence seems to be a protective factor against the burden. To support caregivers, health providers should recognize the expertise of the caregivers and the meaningfulness of this care situation.